2022
DOI: 10.3390/molecules27227752
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols for Livestock Feed: Sustainable Perspectives for Animal Husbandry?

Abstract: There is growing interest in specialized metabolites for fortification strategies in feed and/or as an antioxidant, anti-inflammatory and antimicrobial alternative for the containment of disorders/pathologies that can also badly impact human nutrition. In this context, the improvement of the diet of ruminant species with polyphenols and the influence of these compounds on animal performance, biohydrogenation processes, methanogenesis, and quality and quantity of milk have been extensively investigated through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 167 publications
0
4
0
Order By: Relevance
“…A flavonoid extract from A. sissoo reduced the population of protozoa, resulting in increased propionic acid and a marked decline in methane production, which was comparable with the results of this study [54]. Studies using extracts containing quercetin (the main polyphenol in DAP) have shown a reduction in protozoa, inhibition of methanogen populations, and changes in VFA profiles [55] especially reducing acetate to propionate ratio, which was noticed also in the current study. The inclusion of dietary Indian gooseberry fruit pomace, which is rich in polyphenolic compounds, resulted in lowered methane production in lactating buffaloes [56].…”
Section: Discussionsupporting
confidence: 91%
“…A flavonoid extract from A. sissoo reduced the population of protozoa, resulting in increased propionic acid and a marked decline in methane production, which was comparable with the results of this study [54]. Studies using extracts containing quercetin (the main polyphenol in DAP) have shown a reduction in protozoa, inhibition of methanogen populations, and changes in VFA profiles [55] especially reducing acetate to propionate ratio, which was noticed also in the current study. The inclusion of dietary Indian gooseberry fruit pomace, which is rich in polyphenolic compounds, resulted in lowered methane production in lactating buffaloes [56].…”
Section: Discussionsupporting
confidence: 91%
“…A second 18:2 PUFA was detected, although as a minor constituent. Its identity could be ascribed to rumenic acid, the main conjugated linoleic acid (CLA), deriving from microbial metabolic processes occurring within the digestive tracts of ruminants and accumulating in the mammary gland [30]. Thus, it can be found in milk and dairy products, like yogurt or cheese, as well as vaccenic acid produced by the biohydrogenation processes in rumen, whose concentration is strongly influenced by cow feed.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that they might have multiple modes of action, interfering with several cell signalling pathways [ 37 , 38 , 39 , 40 , 41 ]. Although several studies have been conducted on polyphenols’ positive effects in human medicine [ 42 , 43 ] and animal farming [ 44 , 45 , 46 , 47 ], only marginal attention has been paid to the underlying molecular mechanisms, which are not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%